Prediction of optimum roughage to concentrate ratio in sweet sorghum (Sorghum bicolor L. Moench) bagasse based total mixed ration for buffaloes using in vitro gas technique (Journal of Advanced Veterinary and Animal Research, 2014)
The in vitro gas technique was used to predict the efficiency of sweet sorghum (Sorghum bicolor L. Moench) bagasse (SSB) based total mixed ration comprising different ratios of roughage and concentrate, with the objective of identifying optimum ratio for feeding buffaloes. Eight rations were prepared with roughage to concentrate ratio of 100:0 to 30:70. Significantly (p